Excess Return Market Adjusted Model: Studi Peristiwa Penyerangan Rusia ke Ukraina - Suroto Suroto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This research applies the event study method to the Russian attack on Ukraine, with a focus on empirical evidence regarding the existence of abnormal returns around the event, as well as differences in abnormal returns before and during the event. This research is census in nature, involving 45 stocks that are members of the Liquid 45 Index as the population. Data collection is carried out through secondary sources, including daily closing stock prices and daily IHSG. Data analysis is based on a parametric statistical approach, namely one sample t-test and paired sample t-test. Statistically, this research finds evidence of abnormal returns, although not significant, around the event of Russia's attack on Ukraine. Additionally, there is an insignificant anomaly between the abnormal returns before and during the event. The conclusion of this research is that the Indonesian capital market is said to be an informationally efficient, semi-strong market. These findings can be a reference for investors in allocating funds, aiming to obtain an optimal portfolio.